Urban Agriculture Education and Youth Civic Engagement in the U.S.: A Scoping Review - Russ, Alex; Gaus, Madeline B. (Frontiers in Sustainable Food Systems, 2021)
Urban agriculture education is increasingly used to foster civic engagement among youth. To better understand empirical research on this topic, we analyzed peer-reviewed journal articles that focus on civic engagement among high-school-age students in urban agriculture education programs in the U.S. Using a scoping review approach, we identified 10 relevant research articles published between 2004 and 2018. These articles show that urban agriculture education programs prepare youth for future civic engagement, including by enhancing their understanding of social justice and community assets, and by building their leadership skills. In addition to promoting skills for future civic engagement, these programs engage youth in current civic actions in their neighborhoods, such as creating community gardens and donating food. Although the long-term effect of these programs on youth is still unclear, analyzed articles offer convincing evidence that urban agriculture education programs can be instrumental in helping youth become involved in addressing social and environmental issues in their communities.